Comparison of Family Communication Patterns and Personality Characteristics among Couples Applying for Divorce and a Control Group - Somayeh Ashrafian-Lak; Nasrin Bagheri (Shahid Beheshti University of Medical Sciences, 2021)
Background and Objective: Inefficient communication patterns and personality traits can cause repetitive conflicts among couples. The purpose of this study was to compare the patterns of family communication and personality traits among couples applying for divorce with a control group. Materials and Methods: This research is a descriptive-comparative study. The statistical population consisted of all divorce applicants who were referred to the family courts of Tehran in 2018 and a control group. The research sample consisted of 200 divorce applicants and a control group who were selected via convenience sampling method. The data were collected using a relationship patterns questionnaire, personality characteristics questionnaire, and analyzed by one way ANOVA and SPSS software version 22. Results: The mean (SD) age was 5.7 (8.2) in the control group and 36.7 (9.1) among divorce applicant. The mean (SD) constructive mutual score in the control group was 37.4 (5.5) which was higher than the divorce applicants 35.8 (4.4), P<0.001. The mean (SD) avoidance score in the control group was 27.2 (3.7) which was lower than the divorce applicants 32.4 (6.8), P<0.001. The mean (SD) expectation/withdrawal score in the control group was 24.4 (4.6) which was lower than the divorce applicants 31.5 (5.9), P<0.001. Among the divorce applicants, the components of personality traits included psychosis 35.1 (5.9), extraversion 37.7 (8.1), openness to experience 38.8 (7.9) which were higher than psychosis 30.4 (6.5), extraversion 31.2 (5.6), and openness to experience 32.1 (6.4) in the control group, P<0.001. In addition, the components of consensus were 39.1 (9.2) and conscientiousness 41.3 (9.1) in the control group which was higher than consensus 32.3 (7.1) and conscientiousness 34.4 (7.6) among divorce applicants, P<0.001. Conclusion: The study showed that divorce applicants have a higher expectation/withdrawal from mutual avoidance, but have less interactive relationship. Individuals seeking divorce had higher scores of psychosis, outspokenness, and openness to experience and had lower consensus and conscientiousness.